SHOPPING ORIENTATION, STATUS CONSUMPTION AND IMPULSE BUYING OF GENERATION X AND Y IN PURCHASING FAST FASHION PRODUCTS - Widjojo Suprapto; Ratih Indriyani; Melyvia Santoso (Institute of Research and Community Outreach - Petra Christian University, 2021)
Generation cohorts have different tendencies in purchase behaviors, especially the Generation X and the Generation Y. Although the age gap between these two generation cohorts is not wide, the Generation X has distinctive purchase behaviors that are different from the Generation Y. In the fashion business, the Generation X consumers do not consider the brands in purchasing their clothes, but they calculate the benefits in buying a clothing product. However, the Generation Y consumers consider it as a part of their social status, therefore, they position themselves in the middle class or the upper class by what they wear. The aim of this research is to investigate the different purchase behaviors of the Generation X and Y in buying fast fashion products in Surabaya. The purchase behaviors are reflected through such variables as shopping orientation, status consumption, and impulse buying. As this is a quantitative research, the data are collected using questionnaires that are distributed to 100 respondents. The respondents are chosen using the purposive sampling technique. Then, the data are tested for the validity, reliability, normality, and homogeneity. To test the hypothesis, the independent samples t-test is used. The results show that the differences between the Generation X and the Generation Y are significant in their shopping orientation and impulse buying. However, there are no significant differences in the status consump-tions.